Quantifying water erosion’s impact on soil productivity of croplands in China - Yang Xue; Duan Xingwu; Liu Baoyuan; Xie Yun; Siemann Evan; Wang Hongna; Zhang Enwei; Rong Li; Li Yawen; Feng Detai; Lv Huanxu (National Science Open)
Soil degradation in croplands caused by water erosion significantly threatens food security. However, quantitative effects of current and future water erosion on soil productivity in croplands remain uncertain. Herein, we used 2473 soil series profiles across China to develop a quantitative method to assess the spatiotemporal characteristics of soil productivity affected by water erosion. Results showed that the productivity of 90.5% of typical soil series in China notably decreased due to water erosion. The current annual variation rate in soil productivity due to water erosion averages 10%, with a maximum of up to 33%. The Northeast Black Soil area, the Loess Plateau, and the Southwest Red Soil mountainous area face the highest risk of soil productivity degradation due to future water erosion. These high-risk regions coincide with China’s demographic dividing line (Hu Line). This study highlights the urgent need for targeted soil conservation strategies in these high-risk regions to prevent soil productivity loss and ensure sustainable agricultural practices.